Two doses of pamidronate in infants with osteogenesis imperfecta. Issue 5 (18th December 2007) - Senthilnathan, S; Walker, E; Bishop, N J
Abstract : Introduction: Current regimens of intravenous pamidronate for infants and children with osteogenesis imperfecta (OI) typically deliver 3–12 mg/kg/year of drug. We wished to ascertain the effect of pamidronate at 6 or 12 mg/kg/year on skeletal health in infants with OI. Methods: We recruited 12 infants over a period of 4 years. Infants received either 6 or 12 mg/kg/year of pamidronate. Bone outcomes were assessed by skeletal surveys and DXA bone density measurements at baseline and at 12 months. Results: Bone mass increased in both groups. Infants receiving 12 as opposed to 6 mg/kg/year pamidronate had increased spine bone density after adjusting for covariates at study entry (p = 0.04). Crush fractures improved or remained unchanged in all but one infant. Biochemical markers of bone turnover fell but remained within or above the normal range for age. Metaphyseal remodelling was not impaired. Conclusions: Pamidronate dose in infants may influence lumbar spine bone acquisition. Pamidronate improved vertebral size after prior crush fracturing and did not over-suppress bone turnover.